Rebecca - Maurier, Daphne DU (University Press Plc, 2007)
Rebecca narrative takes the form of a flashback. She lives in Europe with her husband, Maxim de Winter. Rebecca was his first wife. Mrs and Mr Maxim share beautiful memories of their home called Manderley, which has been destroyed by fire. Rebecca's death is woven around this beautiful country house. The book is a spellbinding blend of mystery, horor, romance and suspense. How Rebecca died? What actually happened to her?...
Keywords: Juvenile Fiction